Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1002/sia.740230710
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of the O2+‐induced topography of GaAs and other III–V semiconductors: An STM study of the ripple formation and suppression of the secondary ion yield change by sample rotation

Abstract: Roughening procedures including the early stage of the O,+-induced ripple formation of GaAs were studied quantitatively by scanning tunnelling microscopy (STM). Detailed examinations of the beginning of topography develop ment using fast Fourier transform of the STM images revealed that the ripple formation was not caused by any accidental defects, particles or original irregularity on the substrate, but solely by the conditions of the ion b e a m A systematic investigation of the rippled GaAs surface produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…These results were corroborated by Karen et al [8][9][10], who investigated ripple formation on GaAs surfaces under bombardment with 10.5 keV O + 2 ions. They found that ripple formation takes place for angles of incidence between 30…”
Section: A Ripple Formationsupporting
confidence: 71%
See 2 more Smart Citations
“…These results were corroborated by Karen et al [8][9][10], who investigated ripple formation on GaAs surfaces under bombardment with 10.5 keV O + 2 ions. They found that ripple formation takes place for angles of incidence between 30…”
Section: A Ripple Formationsupporting
confidence: 71%
“…[8][9][10]. The experiments indicate that the ripple wavelength is linear in the energy, following ℓ ∼ ǫ cos θ.…”
Section: A Ripple Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sapphire ripple wavelength increases with ion energy at low temperature, which is consistent with observations for ion eroded SiO 2 , GaAs and Si surfaces. 19,24,25 The data obtained from high/low flux ion sources overlap within experimental error at both 500 eV and 1000 eV, which indicates that the ripple wavelength is independent of incident ion flux at low temperature. A non-linear least squares fit gives a power law coefficient with p=0.71 for the dependence of the wavelength on ion energy (ℓ x ∼ ε p ).…”
Section: B Ripple Wavelength Variation With Ion Energymentioning
confidence: 85%
“…Careful calculations of the energy distribution by molecular-dynamic simulations are necessary to clarify to what extent is underestimated by TRIM. For oblique incidence ion sputtering the energy dependence of the characteristic wavelength has been investigated by several groups. 6,27 Theoretically the characteristic wavelength is obtained from the more complicated anisotropic KS equation, which makes the results more sensitive to specific parameter differences than under isotropic sputtering conditions. e.g., Vajo et al investigated the energy dependence of the characteristic wavelength for Si ͑100͒ surfaces in the energy range of 1.5 to 7 keV.…”
mentioning
confidence: 99%